(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Introduction: Violence against women effects marital relationships. The present study aims to find out the relation between psychological, physical, sexual violence, control over life and decision of marital separation in women victims of domestic violence. Method: Descriptive correlational design was used. A sample of 80 women domestic violence victims selected by using purposive sampling method from rural areas of State Haryana, India. Indian family violence and control scale given by Kalokhe et al. (2016) was used to measure different forms of violence namely, psychological, physical, sexual violence and control. Marital status inventory by Weiss & Cerreto (1980) was used to know the present state of women in regards to their decision of marital separation. Result: Pearson correlation and regression analysis was done to analyse the data. Psychological, physical, sexual violence, was positively correlated with decision of marital separation. Control over life was negatively correlated with decision of marital separation. Physical violence and control over life were the predictors in decision of marital separation. Conclusion: Women in the rural areas are not aware to different forms of violence that are happening in their homes. It is important to do advocacy and awareness about the same.